PENGARUH VARIASI KONSENTRASI CMC Na SEBAGAI PENGIKAT DALAM PASTA GIGI EKSTRAK ETANOLIK DAUN JAMBU BIJI (Psidium guajava L.) DAN EKSTRAK ETANOLIK DAUN SIRIH MERAH (Piper crocatum Ruiz dan Pav) TERHADAP KARAKTERISTIK FISIKNYA - Dewi Andini K.M.; Mimiek Murrukmihadi; Nur Laili; Diana Cholida (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2016)
ABSTRACT Sodium Carboxymethyl  Cellulose (CMC Na) commonly used as  binder  on toothpaste becauseits has good viscosity. The active ingredient of two type of toothpaste is ethanol extract of guava leaves (EEDJB) and ethanol extract of red betel leaf (EEDSM), respectively which has the potential for antiplaque on teeth. The purpose of this study to determine the effect of variations concentration of CMC Naagainst  physical characteristics  from  toothpaste EEDJB and EEDSM. EEDJB and EEDSM  had made by maceration method  using ethanol 70%  as a solvent. Three different concentrations of CMC Naof  toothpaste formulation EEDJB are FI (0.5%); FII (0.75%); FIII (1.00%) and EEDSM are FI (0.45%); FII (0.67%); FIII (0.90%). Toothpaste of EEDSM and EEDJB  had  tested against its physical characteristics. Based on theexperimental results of toothpaste formulations EEDJB and EEDSM states that the higher concentration of CMC  Na hadn’t affect the organoleptic and foaming test, but the viscosity becomes higher and  the potency dispersive of becomes  decreases. Value  of  viscosity (dPas) toothpaste EEDJB for FI (123,33 ± 5,77); FII (256,67 ± 20,81); FIII (283,33 ± 10,40), while  toothpaste EEDSM for FI (125±5); FII (250±25); FIII (316,6± 28,87. The average of the potency dispersive  (cm2) of  toothpaste EEDJB with a load of 150 grams for F1 (1,75); F2 (1,21); F3 (0,89), while toothpaste EEDSM with a load of 150 grams for F1 (1,64); F2 (1,26); F3 (0,73). Keywords :    CMC Na, ethanolic extract of guajava leaves, ethanolic extract of red betle leaves, toothpaste